A comprehensive review on lotus seeds (Nelumbo nucifera Gaertn.): Nutritional composition, health-related bioactive properties, and industrial applications - Sneh Punia Bangar; Kyle Dunno; Manoj Kumar; Hussein Mostafa; Sajid Maqsood (Journal of Functional Foods, 2022)
Lotus is a member of a small family of Nelumbonaceae and is regarded as a sacred flower grown as a freshwater aquatic plant. All plant parts are utilized as food and medicine. Lotus seed (LS) is an important part of the lotus plant due to its nutritional and bioactive components. The presence of phenolic compounds imparts numerous bioactivities to the LS extracts. Nutritional composition is considered crucial for evaluating new ingredients for food applications. Hence, the review deals with the nutritional composition of the LS and bioactivities of LS extracts, viz., anti-cancer, anti-proliferation, anti-diabetic, anti-inflammatory, neuroprotective, antioxidant, and immunomodulatory action. LS also possesses a significant amount of industrially important components which are beneficial for the formulation of food products. The overall profile of the lotus seed makes them potential nutraceutical and bioactive food ingredients. Utilizing this low-cost horticultural waste for producing value-added products is a novel step in its sustainable utilization. The article aimed to comprehensively collate some of the vital information published on lotus seeds incurred in the agri-food sector and critically discussing the potentiality of tapping bioactive compounds from lotus seeds considered as wastes and/or by-products in the entire agriculture-based food sector.